Machado–Joseph disease in a Nigerian family: mutational origin and review of the literature - Ogun, Shamsideen Abayomi; Martins, Sandra; Adebayo, Philip B; Dawodu, Clara O; Sequeiros, Jorge; Finkel, Michael F (European journal of human genetics : EJHG, 2015)
Machado-Joseph disease (MJD) has been described in Africans, but no cases have been reported from Nigeria. Current MJD global distribution results from both the ancestral populations-of-origin and the founder effects of mutations, some as a consequence of the Portuguese sea travels in the 15th to 16th century. Two main ancestral haplotypes have been identified: the Machado lineage, which is more recent, predominant in families of Portuguese extraction, and the Joseph lineage, which is much older and worldwide spread, postulated to have an Asian origin. We report a Nigerian family with MJD from Calabar, once settled by Portuguese slave traders, and assessed its mutational origin. The proband was a 33-year-old man with progressive unsteady gait, weakness of all limbs, dysphagia, dysarthria, urinary frequency and diaphoresis. He had end-of-gaze nystagmus, spastic quadriparesis and atrophic small muscles of the hand. He showed fibrillation potentials on EMG, and nerve conduction studies suggested a central axonopathy without demyelination. This family bears the Joseph haplotype, which has a founder effect in the island of Flores, in the Azores (and their descendants in North-America), but is also the most common in non-Portuguese populations worldwide, with an estimated mutation age of around 7000 years.